Conserving the historic landscape of yangon central business district and historic centre of Vienna - Su Su, Su Su; Stiles, Richard (2008)

(untitled)
This paper highlights the key problems in heritage conservation of the historic areas in Yangon especially Yangon Central Business District (CBD) and factors influencing the management and conservation of historic landscape in Yangon, Myanmar, such as historic impacts of planning and development ideologies and the regulative effects of planning instruments and organizational structures. Revising numerous documents, reports and field observation revealed the problems of CBD in relation to conservation of historic landscape. The conservation of historic urban landscape concept had been reviewed from the international definitions and standards and guidelines and current initiatives for the conservation of historic landscapes. The research critically reviewed the legislations and institutional arrangements concerning with conservation and management of historic core areas of cities such as Yangon CBD and historic core of Vienna. The research also investigated how international practice in conservation such as historic urban landscape management can be modified to be relevant for conserving Yangon CBD. Questionnaires were sent to concerned people from Yangon to get their opinions and views on measures for proper planning legislation for conservation of historic urban landscape. The research highlighted on how shortcomings in Yangon CBD´s planning and conservation legislation address conservation of historic urban landscape. Finally, research investigated the effectiveness of current planning legislations for conservation, with reference to representative cross-sections of Yangon CBD and historic centre of Vienna and recommendations had been given regarding the implications for integrating the conservation of historic city centre concept into Yangon CBD´s planning and management system.